Pengaruh Store Atmosphere dan Kualitas Pelayanan terhadap Keputusan Pembelian - Ardiana, I Putu Yudi; Suartina, I Wayan; Premayani, Ni Wayan Wina (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The problems and objectives of this research are to determine the influence of store atmosphere and service quality on purchasing decisions at the Men Rapeg restaurant in Ubud, Gianyar. The population in this research is all the unknown number of Men Repeg Restaurant consumers. The sample used in this research was 75 respondents. The data in this research was collected through observation, interviews, questionnaires and then tested using multiple linear regression analysis techniques. Based on the research results, it can be seen that store atmosphere has a positive and significant effect on purchasing decisions for the Men Rapeg Restaurant in Ubud, Gianyar. Service quality has a positive and significant effect on purchasing decisions for the Men Rapeg Restaurant in Ubud Gianyar. Store atmosphere and service quality simultaneously have a positive and significant influence on purchasing decisions for the Men Rapeg Restaurant in Ubud Gianyar. The magnitude of the influence of the independent variable on purchasing decisions is 83.3%. Suggestions that can be given to the Men Rapeg Restaurant in Ubud Gianyar are to add lighting to the area around the restaurant so that the view of consumers who are shopping is clearer because there are lights around the restaurant, especially at night.